2013
DOI: 10.1007/s00381-013-2159-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of 5-aminolevulinic acid fluorescence guidance in resection of pediatric brain tumors

Abstract: The off-label use of 5-ALA fluorescence guidance in pediatric patients appears to be most useful in recurrent high-grade gliomas. Fluorescence accumulation in other pediatric brain tumor entities is not predictable and should be evaluated in future clinical studies before being integrated into the current treatment protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 12 publications
4
31
0
6
Order By: Relevance
“…This was also observed in a Preuss et al study, which reported a consequent series of 18 children that were operated on with FGR . The Preuss data even suggested that improved survival parameters were observed after total GBM resections using FGR . No adverse effect was observed in these studies .…”
Section: Photodynamic Diagnoses With 5‐aminolevulinic Acid: How It Worksupporting
confidence: 63%
See 2 more Smart Citations
“…This was also observed in a Preuss et al study, which reported a consequent series of 18 children that were operated on with FGR . The Preuss data even suggested that improved survival parameters were observed after total GBM resections using FGR . No adverse effect was observed in these studies .…”
Section: Photodynamic Diagnoses With 5‐aminolevulinic Acid: How It Worksupporting
confidence: 63%
“…The Preuss data even suggested that improved survival parameters were observed after total GBM resections using FGR . No adverse effect was observed in these studies . None of these publications reported positive fluorescence levels in pilocytic astrocytomas .…”
Section: Photodynamic Diagnoses With 5‐aminolevulinic Acid: How It Workmentioning
confidence: 78%
See 1 more Smart Citation
“…To date, 120 cases applying 5ALA in pediatric brain tumors have been published (Table 1) [4][5][6][7][8][9][10][11][12]. Most publications have included only a handful of cases.…”
Section: Literature Reviewmentioning
confidence: 97%
“…As a result of these extensive preliminary findings, fluorescence-guided resection is increasingly practiced as a surgical adjunct for treatment of adult gliomas in Europe. Recent studies have also begun extending the technique to the pediatric population for microsurgical resection of highly invasive tumors such as medulloblastoma (Beez et al, 2014;Preuß et al, 2013). Initial results suggest administration of 5-ALA generates fluorescence in anaplastic astrocytoma, glioblastoma, medulloblastoma, and anaplastic ependymoma comparable to the adult population (Beez et al, 2014).…”
Section: Figurementioning
confidence: 95%